2014
DOI: 10.1080/10610278.2013.872782
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the transmembrane transport of nucleosides

Abstract: Nucleoside analogues are used as drugs. Due to their hydrophilicity, nucleosides are poorly permeable to membranes and transporter proteins are required for efficient uptake. One approach towards improving membrane permeability of nucleosides is to use synthetic transporters. We describe ways to control transport of nucleosides across a liquid membrane. Hexanoylguanosine 1 selectively extracts and transports cytidines across a CHCl 3 membrane. Transport catalysed by G 1 was influenced by the nucleoside's sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…As shown in the top trace in Figure b, 11 B NMR of a 50 mM solution of C containing 0.5 equiv of boric acid gave a strong signal at δ 11.8 ppm for the cytidine borate (CB) diester (C–B–C) and a signal at δ 8.0 ppm for a CB monoester. These 11 B chemical shifts matched values we have previously reported for cytidine’s borate esters . Solution-state 11 B NMR of a hydrogel made from 50 mM C with 0.5 equiv of both KB­(OH) 4 and AgNO 3 (lower trace in Figure b) showed severely broadened 11 B NMR signals in the δ 8–12 ppm range.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…As shown in the top trace in Figure b, 11 B NMR of a 50 mM solution of C containing 0.5 equiv of boric acid gave a strong signal at δ 11.8 ppm for the cytidine borate (CB) diester (C–B–C) and a signal at δ 8.0 ppm for a CB monoester. These 11 B chemical shifts matched values we have previously reported for cytidine’s borate esters . Solution-state 11 B NMR of a hydrogel made from 50 mM C with 0.5 equiv of both KB­(OH) 4 and AgNO 3 (lower trace in Figure b) showed severely broadened 11 B NMR signals in the δ 8–12 ppm range.…”
Section: Resultssupporting
confidence: 85%
“…The 1 H NMR spectra of C (50 mM) in the presence of varying amounts of KB­(OH) 4 are clearly different (Figure c, traces on left). Chemical shifts for the C ribose H1′ are diagnostic for borate ester formation, as the addition of increasing amounts of KB­(OH) 4 gave new signals at δ 5.84 (d, J = 3.1 Hz) for the borate monoester CB and two doublets, in a 1:1 ratio, between δ 5.7–5.9 (d, J = 2.9 Hz) for the 2 diastereomeric C–B–C borate diesters . As depicted in Figure c (upper trace on right), samples that formed hydrogels in the NMR tube (50 mM C with 0.5 equiv of KB­(OH) 4 and AgNO 3 ) showed significantly broadened and decreased intensity NMR signals for both the C–B–C borate diesters and the CB monoester, again indicating that the C borate-ester species are now major components of the gel network and can no longer be observed via solution-state NMR …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been reported that added sugars including ribose 65 and especially galactose and lactose 66 can enhance the solubility of adenine in water by using CH-p interactions 67 that disrupt the base stacking processes that lead to adenine aggregation. 68,69 In addition, supramolecular chemistry approaches, 70 including using Rebek/Kemp triacid receptors, 71 cyclodextrins 72,73 and biodegradable polymers 74 have been exploited to increase the water solubility of adenine and enhance its transport across biological membranes.…”
Section: Addition Of Nucleobases Into Gák + Borate Hydrogelsmentioning
confidence: 99%